Implementasi Kegiatan Ekstrakurikuler Kitab Kuning sebagai Penguat Pembelajaran Fikih di MTsN 1 Kota Kediri - Ahmad Bahrudin Yusuf; Badrus (Universitas Islam Tribakti Lirboyo Kediri, 2026)
This research aims to explore the implementation of extracurricular yellow book study at MTsN 1 Kota Kediri as a means of strengthening fiqh learning. This research employed a qualitative case study method through observation, interviews, and documentation, analyzed inductively and thematically to explore the planning, implementation, and evaluation of the program. The findings reveal that planning was carried out through meetings involving fiqh teachers, the religious team, and homeroom teachers, by selecting Mabadi Fiqih Juz Awal and appointing an instructor. Implementation proceeded in three stages: opening, core activities using the bandongan method, and closing with Q&A and joint prayer. Evaluation was conducted formatively through assessments of activeness, accuracy in interpretation, and practical worship skills. Overall, this activity proved effective in strengthening fiqh learning while fostering students’ religious character, discipline, and worship skills.